Electrochemical Detection of Sialic Acid Using Phenylboronic Acid‐modified Poly(Diaminobenzoic Acid) Electrodes. Issue 4 (14th December 2017) - Broncová, Gabriela; Matějka, Pavel; Němečková, Zuzana; Vrkoslav, Vladimír; Shishkanova, Tatiana V.
Abstract: This study is focused on the electrochemical detection of sialic acid (SA) using electrochemical impedance spectroscopy (EIS) and potentiometric approaches with the polymeric film derived from 3, 4‐diaminobenzoic acid (3, 4‐DABA) and modified with 3‐aminophenylboronic acid (3‐APBA). The polymeric film derived from 3, 4‐DABA was prepared using cyclic voltammetry at 0.5 M H2 SO4 on a platinum disc electrode from 0 to 1.20 V vs. Ag/AgCl and characterized by FTIR‐Raman spectroscopy. It has been found that the polymerization process goes through the amino group and a free carboxyl group serves for the covalent binding of 3‐APBA onto the polymeric backbone. Both the electrochemical approaches independently confirmed the recognition of SA by APBA‐modified PDABA electrodes. In contrast to known electrochemical sensors in the literature, the APBA‐modified PADABA sensor for SA gave a response in the range from 0.025 to 0.998 mM at neutral pH using the EIS method. The decrease in the EIS signal of ca 12 % was observed after two weeks of intensive use. Importantly, the selective APBA‐modified polymeric electrode enabled the use of SA determination in artificial urine samples in a concentration range that is useful for diagnostic purposes, specifically 12–102 μg mL −1 . Abstract :